Interleukin‐7/Interferon Axis Drives T Cell and Salivary Gland Epithelial Cell Interactions in Sjögren's Syndrome. Issue 4 (15th February 2021) - Rivière, Elodie; Pascaud, Juliette; Virone, Alexandre; Dupré, Anastasia; Ly, Bineta; Paoletti, Audrey; Seror, Raphaèle; Tchitchek, Nicolas; Mingueneau, Michael; Smith, Nikaïa; Duffy, Darragh; Cassard, Lydie; et al.
Abstract : Objective: Primary Sjögren's syndrome (SS) is characterized by a lymphocytic infiltration of salivary glands (SGs) and the presence of an interferon (IFN) signature. SG epithelial cells (SGECs) play an active role in primary SS pathophysiology. We undertook this study to examine the interactions between SGECs and T cells in primary SS and the role of the interleukin‐7 (IL‐7)/IFN axis. Methods: Primary cultured SGECs from control subjects and patients with primary SS were stimulated with poly(I‐C), IFNα, or IFNγ. T cells were sorted from blood and stimulated with IL‐7. CD25 expression was assessed by flow cytometry. SG explants were cultured for 4 days with anti–IL‐7 receptor (IL‐7R) antagonist antibody (OSE‐127), and transcriptomic analysis was performed using the NanoString platform. Results: Serum IL‐7 level was increased in patients with primary SS compared to controls and was associated with B cell biomarkers. IL7R expression was decreased in T cells from patients with primary SS compared to controls. SGECs stimulated with poly(I‐C), IFNα, or IFNγ secreted IL‐7. IL‐7 stimulation increased the activation of T cells, as well as IFNγ secretion. Transcriptomic analysis of SG explants showed a correlation between IL7 and IFN expression. Finally, explants cultured with anti–IL‐7R antibody showed decreased IFN‐stimulated gene expression. Conclusion: These results suggest the presence of an IL‐7/IFNγ amplification loop involving SGECs and T cells in primary SS. IL‐7 was secreted by SGECs stimulated with type I or type II IFN and, in turn, activated T cells that secrete type II IFN. An anti–IL‐7R antibody decreased the IFN signature in T cells in primary SS and could be of therapeutic interest.